2017
DOI: 10.1016/j.bbadis.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin neurons: Multiple routes to regulation of metabolism

Abstract: The burden of disability, premature death, escalating health care costs and lost economic productivity due to obesity and its associated complications including hypertension, stroke, cardiovascular disease and type 2 diabetes is staggering [1,2]. A better understanding of metabolic homeostatic pathways will provide us with insights into the biological mechanisms of obesity and how to fundamentally address this epidemic [3–6]. In mammals, energy balance is maintained via a homeostatic system involving both peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 228 publications
(199 reference statements)
0
21
0
4
Order By: Relevance
“…adverse (Manning et al, 2014). The central melanocortin pathway consists of neurons that produce endogenous melanocortin ligands, derived from POMC [adrenocorticotropic hormone (ACTH), melanocyte-stimulating hormone (MSH) α-, βor γ], five types of receptors for melanocortin (MCRs) and the endogenous melanocortin antagonist/inverse agonist AgRP (Shen et al, 2017). The melanocortin signaling is crucial to the appetite regulation and energy balance.…”
Section: Neuropeptides and Their Receptorsmentioning
confidence: 99%
“…adverse (Manning et al, 2014). The central melanocortin pathway consists of neurons that produce endogenous melanocortin ligands, derived from POMC [adrenocorticotropic hormone (ACTH), melanocyte-stimulating hormone (MSH) α-, βor γ], five types of receptors for melanocortin (MCRs) and the endogenous melanocortin antagonist/inverse agonist AgRP (Shen et al, 2017). The melanocortin signaling is crucial to the appetite regulation and energy balance.…”
Section: Neuropeptides and Their Receptorsmentioning
confidence: 99%
“…Within the CNS, neuronal expression of MCR has been characterized most extensively in the central hypothalamic melanocortin pathway, where MC4Rs are the subtype involved in regulation of metabolism [ 5 ] (review). For example, genetic regulation of MC4R expression in cholinergic neurons in several extrahypothalamic brain regions implicate MC4R in regulation of energy balance and glucose homeostasis [ 28 , 62 ].…”
Section: Direct Effects In the Cnsmentioning
confidence: 99%
“…Melanocortins and melanocortin receptors (MCR) have been extensively investigated for their roles in the hypothalamo-pituitary-adrenal axis [ 1 , 2 , 3 , 4 , 5 ], and to a lesser extent in immune cells [ 6 , 7 , 8 , 9 , 10 ] and the nervous system outside the hypothalamic axis [ 3 , 11 , 12 ]. We have focused on the expression and function of MCR in oligodendroglia (OL), the myelin producing cells of the central nervous system (CNS), with the goal of identifying new therapeutic approaches to decrease CNS damage in multiple sclerosis (MS) as well as to promote repair.…”
Section: Introductionmentioning
confidence: 99%
“…Rodent experiments showed that Mc4r knockout mouse exhibited hyperinsulinemia, hyperglycemia, and adult obesity syndrome (Srisai et al, 2011). Multiple pathways are involved in the regulation of central melanocortin system in energy homeostasis (Shen et al, 2017). MC4R signaling regulates energy balance through stimulating brain-derived neurotrophic factor (BDNF) expression in the ventromedial hypothalamus (VMH) (Xu et al, 2003).…”
Section: The Melanocortin 4 Receptormentioning
confidence: 99%